2021
DOI: 10.6018/eglobal.479441
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de los pacientes sobre los cuidados de enfermería en el contexto de la crisis del COVID-19

Abstract: Antecedentes: La pandemia de COVID-19 ha alterado considerablemente los procedimientos habituales de los sistemas sanitarios en todo el mundo. El trabajo diario se ha vuelto física y emocionalmente agotador para los profesionales sanitarios, obligados a afrontar y adaptarse a nuevos retos y situaciones estresantes. Esta situación pesa sobre la práctica diaria de enfermería.Objetivo: El presente estudio tuvo como objetivo determinar la percepción del paciente sobre los cuidados de enfermería humanizados recibid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…For this reason, it was important to evaluate the patients' perception of humanised care, and it was found that most of them perceive it to be favourable or moderately favourable. These results coincide with the study by (Blanco-Nistal et al, 2021), who also obtained an overall good perception, despite the negative impact of COVID-19. On the other hand, the indicator of good perception of humanised nursing care is related to the quality and satisfaction of the service provided (Guerrero-Ramírez et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For this reason, it was important to evaluate the patients' perception of humanised care, and it was found that most of them perceive it to be favourable or moderately favourable. These results coincide with the study by (Blanco-Nistal et al, 2021), who also obtained an overall good perception, despite the negative impact of COVID-19. On the other hand, the indicator of good perception of humanised nursing care is related to the quality and satisfaction of the service provided (Guerrero-Ramírez et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to the dimensions of emotional support, proactivity, nurse characteristics and prioritises being cared for, the majority were favourable and moderately favourable, with emotional support standing out in the unfavourable opinions. These results coincide with the study of Blanco-Nistal et al, (2021), who in each dimension of humanised care, highlighted a good level in the qualities of caring practice, openness to nurse-patient communication and willingness to care. On the other hand, Almanza-Rodríguez, (2020), argue that nursing professionals and the health care team are articulating care actions that provide confidence and security in the face of the risks of nosocomial infections (Ospina Vanegas et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this regard, in the study of Mena Hassan Ebrahim et al (6) in 2021 and Azizi et al 25 in 2018, the most points were given to the field of professional knowledge and skills, and these results are in line with the results of the present study. The results of Marta Maria Blanco et al's 32 research in Spain 2021 titled Patient's understanding of nurses’ caring behavior in the Covid-19 crisis, the findings of this study indicate patients’ satisfaction with nurses’ caring behaviors. Also, the results of the study by Parizad et al 33 in 2020 under the title of satisfaction with nursing care and factors related to it in patients with covid-19 in Urmia also indicate the average satisfaction of patients (68.9%) with nursing care and knowledge and It is their professional skill.…”
Section: Discussionsupporting
confidence: 55%
“…It is a data collection that the organism receives as primary information and which attributes meaning through cognitive processes (Monje et al, 2018). In other words, perception is a mental picture shaped by human experience, structural forms, culture, and needs (Blanco et al 2021).…”
Section: Introductionmentioning
confidence: 99%